2022
DOI: 10.1111/jgh.16035
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based intensive nutrition therapy improves frailty and sarcopenia in patients with decompensated cirrhosis: A randomized clinical trial

Abstract: Babu Lal Meena and Sunil Taneja equally contributed as first authors. This study was registered with the Clinical Trial Registry of India (ctri.nic.in/Clinicaltrials/2019/ 05/019387). Declaration of conflict of interest: None. Author contributions: ST conceptualized the study design, interpreted the data, drafted the manuscript, and did critical revisions. PT conceptualized the study design, interpreted the data, and did critical revisions. BM contributed to the acquisition, analysis, and interpretation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…94 Similarly, Meena et al explored the influence of a 6-month dietician-supported home-based intensive nutrition therapy on patients with decompensated cirrhosis. 95 The indicated intervention gave rise to statistically and clinically relevant improvement in frailty determined by the LFI, mirrored as increased body weight, muscle strength, and physical performance.…”
Section: Pre Vention Manag Ement and Tre Atment Of Fr Ailt Ymentioning
confidence: 98%
See 1 more Smart Citation
“…94 Similarly, Meena et al explored the influence of a 6-month dietician-supported home-based intensive nutrition therapy on patients with decompensated cirrhosis. 95 The indicated intervention gave rise to statistically and clinically relevant improvement in frailty determined by the LFI, mirrored as increased body weight, muscle strength, and physical performance.…”
Section: Pre Vention Manag Ement and Tre Atment Of Fr Ailt Ymentioning
confidence: 98%
“…A pilot double‐blind study implicated that BCAAs supplementation alongside physical activity for 12 weeks significantly improve the LFI in entire cohort, wherein some respondents even achieved resolution of baseline frailty 94 . Similarly, Meena et al explored the influence of a 6‐month dietician‐supported home‐based intensive nutrition therapy on patients with decompensated cirrhosis 95 . The indicated intervention gave rise to statistically and clinically relevant improvement in frailty determined by the LFI, mirrored as increased body weight, muscle strength, and physical performance.…”
Section: Prevention Management and Treatment Of Frailtymentioning
confidence: 99%
“…Limited data exist on the impacts of nutritional interventions in sarcopenic patients as it pertains to mortality. A 6-month RCT of home-based intensive nutrition therapy in decompensated cirrhosis patients demonstrated that patients who remained adherent to calorie and protein intake targets within the intervention arm showed superior survival compared to those who did not have nutritional intervention (96.8 vs. 78%, P ¼ 0.04) [46]. ALthough there remains a paucity of literature in the field, the current consensus guidance for patients with end-stage liver disease includes avoiding periods of starvation with bedtime feeding, enteral feeding and parenteral nutrition as well as advising careful exercise [47].…”
Section: Sarcopenia and Prognosismentioning
confidence: 99%
“…Moreover, AASLD recommends a safe protein intake of 1.2-1.5 g/kg/d for adults with cirrhosis, which should come from a diverse range of sources[ 7 ]. A recent randomized controlled trial showed that intensive nutrition therapy administered at home for six months can enhance frailty and sarcopenia in patients with decompensated cirrhosis[ 166 ]. The study found that the intervention group showed a greater improvement in the LFI compared to the control group (0.8 vs 0.4; P < 0.001)[ 166 ].…”
Section: Management Of Frailty In Liver Diseasesmentioning
confidence: 99%
“…A recent randomized controlled trial showed that intensive nutrition therapy administered at home for six months can enhance frailty and sarcopenia in patients with decompensated cirrhosis[ 166 ]. The study found that the intervention group showed a greater improvement in the LFI compared to the control group (0.8 vs 0.4; P < 0.001)[ 166 ]. AASLD highlights the importance of identifying and overcoming obstacles to proper nutrition for patients with cirrhosis who are frail[ 7 ].…”
Section: Management Of Frailty In Liver Diseasesmentioning
confidence: 99%